The RDA workbook : learning the basics of Resource Description and Access - Mering, Margaret (2014)
"Whether a library catalogs its own materials or not, librarians still need to have some understanding of RDA. Designed to be used by academic, public, and school librarians, this is the perfect introduction"--
FRBR, the framework behind RDA / Melissa Moll -- RDA in the real world : preparing bibliographic records / Corinne Jacox, Margaret Mering, Melissa Moll, Emily Nimsakont, and Deirdre Routt -- Creating access points and understanding authority records / Casey Kralik -- Implementing RDA into your library and catalog / Casey Kralik.
Accompanied by a CD-ROM.
Includes bibliographical references, glossary, and index.
Keywords: Resource description & access; Descriptive cataloging -- Standards; Descriptive cataloging -- Standards -- Problems, exercises, etc; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / General; LANGUAGE ARTS & DISCIPLINES / Study & Teaching